Long-Term Mixed Chimerism After Ex Vivo/In Vivo T Cell-Depleted Allogeneic Hematopoietic Cell Transplantation in Patients With Myeloid Neoplasms - Ruhnke, Leo; Stölzel, Friedrich; Oelschlägel, Uta; von Bonin, Malte; Sockel, Katja; Middeke, Jan Moritz; Röllig, Christoph; Jöhrens, Korinna; Schetelig, Johannes; Thiede, Christian; Bornhäuser, Martin (Frontiers in Oncology, 2021)
In patients who have undergone allogeneic HCT, myeloid mixed chimerism (MC) is a risk factor for disease relapse. In contrast, several studies found favorable outcome in patients with lymphoid MC. Thus far, most studies evaluating MC focused on a short-term follow-up period. Here we report the first case series of long-term survivors with MC. We screened 1346 patients having undergone HCT for myeloid neoplasms at our center from 1996 to 2016; patients with data on PBMC/CD4+/CD34+ STR donor chimerism (DC) and follow-up ≥24 months post HCT were included (n=443). We identified 10 patients with long-term MC (PBMC DC)< 95% ≥12 months post HCT), median follow-up was 11 years. All patients had received combined ex-vivo/in-vivo T-cell depleted (TCD) peripheral blood stem cells; none experienced ≥ grade 2 acute GVHD. The mean total, CD4+, and CD34+ DC of all patients was 95.88%, 85.84 %, and 90.15%, respectively. RIC was associated with a trend to lower mean total DC. Of note, two patients who experienced relapse had lower CD34+ DC, but higher CD4+ DC as compared to patients in continuous remission. Bone marrow evaluation revealed increased CD4+/FOXP3+ cells in patients with MC, which might indicate expansion of regulatory T-cells (Tregs). Our results confirm known predictive factors associated with MC such as RIC and TCD, underscore the value of CD34+ MC as a predictor of relapse, highlight the association of CD4+ MC with reduced risk of GVHD, and indicate a possible role of Tregs in maintenance of immune tolerance post HCT.